Effect of spraying with different concentrations of Seaweeds extracts on vegetative growth and yield of two cultivars of Peas (Pisum sativum L.) - Yousif, Kurdistan Hassan (Sulaimani Journal for Pure and Applied Sciences, 2018)
The study was carried out during the2017, spring growing season in the college of Agriculture, University of Dohuk, Kurdistan region, Iraq, to determine the effects of seaweeds extract (Alga 600) on two pea cultivar (Pisum sativum L.) which are Ambrosia(A) and Szesciotygodniowy (B) were grown in plastic bags. Results of vegetative growth characters, quality and yield characteristic showed cultivar (A) gave a high early yield.plant-1(20.77g) compared with (B) cultivar that showed lower yield (16.22g). Plants treated with 4ml.L-1 of seaweeds extracts in the both cultivars gave good results in total yield especially in A cultivar (137.07g) as compared with control which gave lower total yield (94.9g).The results of number of nuduls.plant-1, length of nodules and width of nodules (mm),showed cultivar (A) gave high value which were(22.08, 15.65 and 6.23) respectively which significant different in compared with (B) cultivar. Mineral contents (NPK),cultivar (A) showed high percentages which were (3.67,0.29and 3.33%) respectively, compared to the cultivar B which gave lower percentages (3.37, 0.27 and 3.08%) respectively, and treating plant with 4ml.L-1 resulted in high nitrogen (3.84%) compared to lower value (2.88%) for the control, results of protein%, also cultivar A gave high value of protein percentage (22.74%) compared to the cultivar B (21.06%).
Keywords: Seaweeds extracts; pea cultivar; dry seeds